Modeling and Predicting Total Ozone Column and Rainfall in Kodaikanal, Tamilnadu By Arima ProcessAmongst all weather happenings, ozone plays the very important role in human life as well as climate change. The understanding of Total Ozone Column (TOC) and - K.Thamizharasan,, R.SamuelSelvaraj, Sachithananthem C.P., (International Journal of Engineering and Computer Science, 2017)
Amongst all weather happenings, ozone plays the very important role in human life as well as climate change. The understanding of Total Ozone Column (TOC) and rainfall variability helps the agricultural management in planning and decision- making process. The important aspect of this research is to find a suitable time series seasonal model for the prediction of total ozone column and annual-rainfall in Kodaikanal,Tamilnadu. In this study, Box-Jenkins model is used to build an ARIMA model for predicting the monthly total ozone column and rainfall in Kodaikanal, Tamilnadu with a total of 12 years data. Keywords: ARIMA, Rainfall, Seasonality, Total Ozone Column